Chemotherapy-induced peripheral neuropathy: clinical features, diagnosis, prevention and treatment strategies - Gutiérrez-Gutiérrez, Gerardo; Sereno, María; Miralles, Ambrosio; Casado-Sáenz, Enrique; Gutiérrez-Rivas, Eduardo (Clinical & translational oncology, 2010)
Chemotherapy-induced peripheral neuropathy (CIN) is a common toxicity of anticancer treatment and its incidence is growing. It significantly affects quality of life and is a dose-limiting factor that interferes with treatment. Its diagnosis can be established in clinical terms but some complementary tests can help when the diagnosis is difficult. There is still no proven method to prevent it that has become a standard of care in spite of the huge amount of investigation carried out in recent years. There are promising strategies that could help reduce the burden of this complication. This review will suggest an approach to the diagnosis of these disorders and provide an update on new therapies.